Case Study of Mechanically Stabilized Earth (MSE) Retaining Wall Failure in the State of Tennessee; Recommendations for Future Design and Constructions (Journal of Civil Engineering Researchers, 2023)
This study presents an investigation into the failure of a Mechanically Stabilized Earth (MSE) retaining wall in Tennessee, USA. The wall was constructed to support an embankment development, but it failed catastrophically, causing damage to the road and posing a significant safety risk to the public. The investigation involved a comprehensive site visit, field data collection, laboratory testing, and numerical modeling. Our investigation revealed that the failure of the retaining wall was caused by inadequate construction practices. Specifically, the wall was not constructed in accordance with design specifications, and the backfill material used was not properly compacted. The construction issues resulted in the differential settlement of the wall, which ultimately caused it to fail. Based on our findings, we propose a set of recommendations for the design and construction of future retaining walls in similar geotechnical conditions. The recommendations include the proper selection and use of backfill material, proper compaction of backfill, and adherence to design specifications. The results of this study are expected to contribute to the development of improved design standards and construction practices for MSE retaining walls in Tennessee and other regions with similar geotechnical conditions.
Keywords: Mechanically Stabilized Earth (MSE); Retaining Wall Failure; Case Study; Design and Constructions